Research Trends on Socio-Scientific Issues in Chemistry Learning: A Systematic Review - Dewi, Citra Ayu; Yahdi, Yahdi (Jurnal Pendidikan MIPA, 2025)
Socio-scientific concerns have emerged as a prominent focus in contemporary chemistry education research. This study aims to analyze the trends used in socio-scientific issues in chemistry learning based on the results of research that has been carried out. This study uses a meta-analysis research design. This meta-analysis uses Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). Data was acquired from the Scopus and Google Scholar databases utilizing scholarly publications from esteemed worldwide journals with the Scopus Q1-Q3 classification. Conduct an article search utilizing the title and keywords "Socio-Scientific Issues," "Socio-Scientific Issues Approach," or "Socio-Scientific Issues in Chemistry Learning," covering the last decade from 2015 to 2025. The results indicated that the database had a total of 10,982 articles, from which 35 articles were selected for examination. The results of the review found that: a) socio-scientific issues in chemistry learning have a very dominant relevance to case-based learning, namely inquiry (20.57%), PBL (10.29%) and PjBL (5.14%); b) the application of socio-scientific issues in chemistry learning is more dominant towards the aspects of argumentation, problem-solving, critical thinking and creative thinking. Consequently, the tendency in chemistry education on socio-scientific issues underscores case-based learning that prioritizes contextual difficulties.        Keywords: chemistry, learning, socio-scientific issues.